PENGARUH METODE MASERASI BERTINGKAT TERHADAP NILAI RENDEMEN DAN PROFIL KRAMOTOGRAFI LAPIS TIPIS (KLT) EKSTRAK DAUN KEMANGI (Ocimum basilicum L.) - admin; Zulfahmi Hamka; Raymond Arief (Akademi Farmasi Yamasi Makassar, 2022)
Effect of graded maceration method on yield value and thin layer chromatographic profile (TLC) of basil leaf extract (Ocimum basilicum L.) Research has been carried out related to the effect of the multilevel maceration method on the yield value and thin layer chromatographic profile (tlc) of basil leaf extract (Ocimum basilicum L.). This research method is carried out by observation in the laboratory. This study aims to calculate the yield value and determine the Thin Layer Chromatography Profile (TLC) of basil leaf extract using the stratified maceration method. The samples were macerated in stages with N-hexane and 96% ethanol as solvents. The yield value and thin layer chromatography profile were calculated. The results showed that the NH sample obtained a yield value of 1.34% while the ET sample obtained a yield value of 5.71% which means that the multilevel maceration method affected the extract yield from basil leaves (Ocimum basilicum L.). The results on the Thin Layer Chromatography profile, the spots that produce the most are ET samples with non-polar eluent (ethyl acetate: n-hexane) in a ratio of 3:7 which get 12 spots, while the least spots are NH samples with polar eluents (ethyl acetate: n-hexane) with a ratio of 7:3 which got 4 spots.